1979
DOI: 10.1051/rnd:19790802
|View full text |Cite
|
Sign up to set email alerts
|

The role of the mesonephros in the development of indifferent gonads and ovaries of the mouse

Abstract: Summary. The development of the sexually indifferent gonads and ovaries of the mouse was studied in embryos, fetuses, newborns and prepuberal animals from day 10 post-coitum through post-natal day 32. During the phase of compartmentalization, the mesonephric tubule-ovigerous cord continuum becomes subdivided into independent structures. This is due to maturation of the primitive stroma surrounding the various components of the continuum and its progressive transformation into a thick, fibrous connective tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 18 publications
4
39
0
Order By: Relevance
“…According to some researchers (3,10), the mesonephros contributes cells to the ovarian stroma, and mesonephric tubules may give rise to the follicular cells. In the developing mouse ovary, the mesonephros consists of a connecting complex of tubules in extraovarian and intraovarian locations.…”
Section: Introductionmentioning
confidence: 99%
“…According to some researchers (3,10), the mesonephros contributes cells to the ovarian stroma, and mesonephric tubules may give rise to the follicular cells. In the developing mouse ovary, the mesonephros consists of a connecting complex of tubules in extraovarian and intraovarian locations.…”
Section: Introductionmentioning
confidence: 99%
“…At puberty, preventer activity in the testis would decrease, thus releasing the germinal cells to the meiotic process (3,5). We recently found, however, that the somatic cells ofthe seminiferous cords ofthe testis are mesonephric in origin (9)(10)(11) and, in fact, derive from the same cellular elements that in the female differentiate into the precursors of the granulosa cells (12,13). The demonstration that the somatic cells of the male and female sex cords have the same mesonephric origin and identical differentiation patterns makes it much less easy to accept the hypothesis that they may be the source of substances having antagonistic influences on the germinal cells insofar as meiotic maturation is concerned.…”
mentioning
confidence: 99%
“…Descriptive morphological studies have, furthermore, indicated that mesonephric cell contribution to the developing gonad is independent of the sex. In developing gonads of numerous mammalian species, the presence of 'cell streams' connecting the mesonephros tubuli and the developing gonad is suggested to indicate mesonephric cell contribution to both the ovarian and the testicular somatic cell population [mouse: Byskov et al, 1977;Byskov, 1978a;Upadhyay et al, 1979Upadhyay et al, , 1981Kanai et al, 1989;Karl and Capel, 1995;rat: Stein and Anderson, 1979;pig: Byskov et al, 1986;sheep: Zamboni et al, 1979sheep: Zamboni et al, , 1981Tisdall et al, 1999;human: Wartenberg, 1982;Wartenberg et al, 1991]. The mesonephric part of such 'cell streams' has been proposed to be the predominant cell contributor due to a comparable high mitotic activity [Stein and Anderson, 1979].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of several species have suggested mesenchymal tissue, coelomic epithelium and/or the mesonephros as being the only or participating source of the gonadal somatic cells. These studies are based on experimental evidence [Byskov, 1974;Byskov et al, 1977] or morphological indications [Gondos, 1969;Merchant, 1975;Pelliniemi, 1976;Byskov, 1978a;Upadhyay et al, 1979Upadhyay et al, , 1981Zamboni et al, 1979;Wartenberg, 1982;Yoshinaga et al, 1988;Kanai et al, 1989;Francavilla et al, 1990;Smith and Mackay, 1991;Wartenberg et al, 1991;Karl and Capel, 1995;Magras et al, 1997;Tisdall et al, 1999]. A more direct way of examining somatic cell contribution from either the coelomic epithelium or the mesonephros has been attempted by tracing the migration of cells carrying a marker MerchantLarios et al, 1993;Martineau et al, 1997;Brennan et al, 1998;Karl and Capel, 1998;Merchant-Larios and Moreno-Mendoza, 1998;Tilmann and Capel, 1999;Albrecht et al, 2000].…”
Section: Introductionmentioning
confidence: 99%